Strategy of Development Tourism Based on BOT (Build, Operate, Transfer) In 2018 - Yanur, Murniyati; Zaenuri, Muchammad (Journal of Governance and Public Policy, 2019)
Tourism is one of the large foreign exchange earning fields for the country. The tourism ministry's performance target in 2019 is to bring in 20 million foreign tourists and 275 million local tourists with 260 trillion rupiah in foreign exchange. So that tourism is encouraged both at the Provincial, Regency and village level. This was done to meet the performance target of the ministry of tourism and improve the country's economy. One of the Attractions in West Kalimantan Precisely in the city of Pontianak, which is quite interesting to visit and is a cultural preserve, the Equator Monument. This Equator Monument attraction is one of the mainstay promotions of Pontianak City. To develop the equatorial monument in Pontianak City government in collaboration with several stakeholders to realize the development of a more attractive tourist attraction into the Equator Park. This is one of the reasons for research to see the collaboration carried out in the development and management of the Equator Monument. This research is a qualitative research with a case study approach which intends to see the activities carried out in the daily life of the community and also the interaction process in groups or individuals. Data collection in this study uses the method of observation, interviews and also documentation. Thus, any data that has been collected can be selected and described and conclusions can be drawn. The results of the research related to the cooperation in Build Operate Transfer in the development of tourism in the Equatorial Park showed that there was indeed a collaboration with the City Government and Private Parties. But the key stakeholders who are the driving actors in the development of tourism in Khatuistiwa Park are PT. Mitra Bangun Kota.